PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KEPUASAN KERJA DENGAN MOTIVASI SEBAGAI VARIABEL MODERATING - Handoko, Sunarso & Sumarno Dwi Saputra (Universitas Slamet Riyadi, 2017)
The purpose of this study was to analyze the significance of the effect oftransformational leadership and motivation on job satisfaction of employees, and theeffect of transformational leadership on job satisfaction with motivation are moderatingvariable. This research is a survey on employees UPTD Terminal Tirtonadi Surakarta.The type of data used quantitative and qualitative data. The data source used primarydata sources and secondary data. The study population were employees UPTD TerminalTirtonadi with sample 72 by proportional cluster random sampling technique. Datacollection technique used questionnaire and literature. Data were analyzed usedmultiple linear regression, t-test, F and coefficient of determination and absolutedifference test. The results showed that transformational leadership have a significanteffect on job satisfaction. Motivation has a significant effect on employee satisfaction.Motivation does not moderate the the effect of transformational leadership on employeesatisfaction.Keywords: transformational leadership, motivation, job satisfaction